A escrita de Arnaldo Antunes em seu(s) (40) escritos - Alferes, Sirlene Cíntia (2010)
Aiming at analyzing the process of singularity of utterances produced by Arnaldo Antunes in 40 Escritos, a book which allows us to think about the artistic in its relation to the style, taken as a work with and about the symbolic, this dissertation is theoretically founded in the principles of the Linguistics of Enunciation, notably the studies by Emile Benveniste, in some concepts of Freudo-Lacanian Psychoanalysis, in Philosophy, in French Discourse Analysis, and in Morphology. It is assumed that the symbolic leads to the assumption of singularity in linguistic terms. In such a perspective, this process of singularity, which Arnaldo has been through, seems to stand beyond of what can be conceived as discourse (the place of stability) and as speech (the place of instability). Searching for the features of the artistic creation, Arnaldo strives to mark that the different is also in what is the same. This brings us the possibility of distinguishing that the unusual comprises the usual. In other words, by looking for the artistic creation, it is possible to realize that there is a work with and about the symbolic whose constancy produces a way of writing in which an identity in mo(ve)ment, as a trait of singularity, can be noticed. The analysis has shown that this kind of production undertaken by the author is related to what can not be neglected to do. It has to do with how the subject deals with the language. In addition, it was the relation of Arnaldo with the language, and broadly, with the symbolic, that enabled the analysis to find out that, in 40 Escritos, Arnaldo plays with the language as well as he plays with the symbolic. As a result, such a process of artistic production ends up in (re) creating the symbolic which also comprises linguistic interaction, linguistic (re)creation, and symbolic subversion.